HUBUNGAN ANTARA PENGETAHUAN DAN PERILAKU IBU NIFAS PARITAS I DALAM PERAWATAN NEONATUS - Sondang Lusiana Sitinjak; Monalisa Sitompul (Fakultas Ilmu Keperawatan Universitas Klabat, 2022)
Neonates are the most high-risk period in the first month of life, so knowledge and behavior skills are needed to maintain optimal baby growth and development. The purpose of this study was to find the relationship between knowledge and behavior of postpartum mothers in neonatal care. The design of this study was cross sectional. The sample in this study amounted to 52 people taken by the total sampling method. The research instrument used a knowledge and behavior questionnaire in neonatal care. Pearson product moment statistics were used in hypothesis testing and obtained a significance value of 0.000 and an rcount of 0.477**. Descriptive analysis shows that postpartum mothers have very good knowledge in neonatal care (91.67%), and postpartum mothers have very good behavior in neonatal care (91.56%). The researcher concluded that there was a significant relationship between knowledge and behavior of parity 1 postpartum mothers in neonatal care. The researcher suggests that an in-depth study be conducted on the factors that influence the knowledge and behavior of parity 1 postpartum mothers in neonatal care.